MODERASI TRADISI KONCO WINGKING: UPAYA MELEPASKAN DILEMA - Moh. Faiz Maulana (Jurnal Harkat : Media Komunikasi Gender, 2020)
Abstract: Living in a modern world with a variety of traditions, situations and information has made women in Paciran experience dilemma of the self. On the one hand, modernization gives freedom, on the other hand women must be able to maintain the tradition of their identity as konco wingking. This study recounts the efforts of women in Paciran to moderate the tradition of the konco wingking in maintaining their traditions and identity as Javanese women who started out of their homes to mergawe, but still put the house as the place of origin. The impact of this is the selection of women's work which places the house as the place of return. This research was conducted on six female nguplik workers in Paciran, Lamongan, East Java. The results of the study indicate that the konco wingking through the process of moderating tradition, is able to be displayed in different practices. Konco Wingking, which has been understood only as domestic practices, has expanded into public practices.  Abstrak: Hidup dalam dunia modern dengan berbagai persinggungan tradisi, situasi dan informasi telah membuat perempuan di Paciran mengalami dilemma of the self. Pada satu sisi modernisasi memberikan kebebasan, di sisi lain perempuan harus mampu menjaga tradisi tentang identitasnya sebagai konco wingking. Penelitian ini menceritakan upaya perempuan di Paciran memoderasi tradisi konco wingking dalam mempertahankan tradisi dan identitasnya sebagai perempuan Jawa yang mulai ke luar rumah untuk mergawe, namun tetap menempatkan rumah sebagai yang utama (place of origin). Dampak dari hal tersebut adalah pemilihan kerja perempuan yang menempatkan rumah sebagai tempat utama (place of return). Penelitian ini dilakukan kepada enam perempuan pekerja nguplik di Paciran, Lamongan, Jawa Timur. Hasil penelitian menunjukkan bahwa konco wingking melalui proses moderasi tradisi, mampu ditampilkan dalam praktiknya yang berbeda. Konco wingking yang selama ini dipahami hanya sebagai praktik-praktik domestik telah mengalami perluasan menjadi praktik-praktik publik.